2016
DOI: 10.1007/s00126-016-0698-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyphase vein mineralization in the Fennoscandian Shield at Åkerlandet, Järvsand, and Laisvall along the erosional front of the Caledonian orogen, Sweden

Abstract: The Åkerlandet, Järvsand, and Laisvall deposits in Sweden are calcite-fluorite-sulfide vein deposits and occurrences located close to the current erosional front of the Caledonian orogen and hosted by crystalline basement rocks in the Fennoscandian Shield. At Laisvall, basement-hosted veinlets occur beneath Ediacaran to Cambrian sandstones that host a strata-bound Pb-Zn deposit. The mineralized fractures at Åkerlandet and Järvsand occur along fault systems oriented N–S to NNW–SSE. Veins or veinlets strike NNW–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Direct dating of (a) calcite infill in veins (e.g., Nuriel et al, 2012;Roberts et al, 2020), (b) illite in fault gouge (e.g., Uysal et al, 2020;Viola et al, 2016), (c) illite-K-feldspar-calcite slickenfibres (Tillberg et al, 2020) and (d) sulphides in faults and veins (Saintilan et al, 2017;Vernon et al, 2014) has indicated that episodic reactivation and fluid flow can be constrained by absolute time stamps.…”
Section: Introductionmentioning
confidence: 99%
“…Direct dating of (a) calcite infill in veins (e.g., Nuriel et al, 2012;Roberts et al, 2020), (b) illite in fault gouge (e.g., Uysal et al, 2020;Viola et al, 2016), (c) illite-K-feldspar-calcite slickenfibres (Tillberg et al, 2020) and (d) sulphides in faults and veins (Saintilan et al, 2017;Vernon et al, 2014) has indicated that episodic reactivation and fluid flow can be constrained by absolute time stamps.…”
Section: Introductionmentioning
confidence: 99%